Hi! Fly Guy - Arnold, Tedd. (New York : Scholastic, 2005)
When Buzz captures a fly to enter in The Amazing Pet Show, his parents and the judges tell him that a fly cannot be a pet, but Fly Guy proves them wrong.
"Cartwheel books."
Keywords: Flies -- Fiction; Pet shows -- Fiction